2014
DOI: 10.5935/1676-2444.20140018
|View full text |Cite
|
Sign up to set email alerts
|

Mucins and NCAM (CD56) in intrahepatic cholangiocarcinogenesis

Abstract: Introduction: Cholangiocarcinoma is the second most common malignant neoplasm of the hepatobiliary system. During cholangiocarcinogenesis phenotypic changes occur in the ductal epithelium, including the expression of mucins (MUC). However, the evaluating studies of the expression of mucins in the different stages of cholangiocarcinogenesis are scarce. CD56 has also contributed in differentiating benign ductal proliferation and cholangiocarcinoma; however, its expression has not been evaluated in dysplastic epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A total of 341 papers were identified, of which 148 were retrieved for full-text review. Among these 148 publications, 16 studies6 7 9 10 12–15 31 32 34–37 54 55 were eligible for the meta-analyses according to the inclusion and exclusion criteria. Nine studies7 9 10 12–15 36 37 out of 16 studies used OS as endpoint, and eight studies6 9 31 32 34 35 54 55 used the sensitivity and specificity rate as the endpoint (one study reported by Huang et al also provided the data on diagnostic value of MUC1 in tissue).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 341 papers were identified, of which 148 were retrieved for full-text review. Among these 148 publications, 16 studies6 7 9 10 12–15 31 32 34–37 54 55 were eligible for the meta-analyses according to the inclusion and exclusion criteria. Nine studies7 9 10 12–15 36 37 out of 16 studies used OS as endpoint, and eight studies6 9 31 32 34 35 54 55 used the sensitivity and specificity rate as the endpoint (one study reported by Huang et al also provided the data on diagnostic value of MUC1 in tissue).…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of eligible studies and their participants were listed in tables 1, table 2 and table 3. A total of nine studies7 9 10 12–15 36 37 evaluating the prognostic value of MUC1 for resectable CCA were conducted in four countries (Korea, Japan, China and Thailand), the other seven studies6 31 32 34 35 54 55 investigating the diagnostic capability of WFA-MUC1 were undertaken in five countries (Japan, UK, Brazil, Thailand and China). Retrospective study design was applied to perform the meta-analysis of prognostic value by all selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this edition of JBPML, you will find a paper entitled "The mucins and NCAM (CD56) in intrahepatic colangiocarcinogênese" (1) , in which the participation of different types of mucins and some adhesion molecules (NCAM) expressed in bile ducts is discussed as differential markers between reactive and dysplastic processes (3) . In addition, a particular type of mucin, MUC1 was associated with the presence of metastases, loss of differentiation and more invasive behavior of the tumor, worse prognosis, which would be reflected in reduced survival (4) .…”
Section: Adagmar Andriolomentioning
confidence: 99%